Palmitoylation of A-kinase anchoring protein 79/150 modulates its nanoscale organization, trafficking, and mobility in postsynaptic spines - Chen, Xiaobing; Crosby, Kevin C.; Feng, Austin; Purkey, Alicia M.; Aronova, Maria A.; Winters, Christine A.; Crocker, Virginia T.; Leapman, Richard D.; Reese, Thomas S.; Dell’Acqua, Mark L. (Frontiers in Synaptic Neuroscience, 2022)
A-kinase anchoring protein 79-human/150-rodent (AKAP79/150) organizes signaling proteins to control synaptic plasticity. AKAP79/150 associates with the plasma membrane and endosomes through its N-terminal domain that contains three polybasic regions and two Cys residues that are reversibly palmitoylated. Mutations abolishing palmitoylation (AKAP79/150 CS) reduce its endosomal localization and association with the postsynaptic density (PSD). Here we combined advanced light and electron microscopy (EM) to characterize the effects of AKAP79/150 palmitoylation on its postsynaptic nanoscale organization, trafficking, and mobility in hippocampal neurons. Immunogold electron microscopy (EM) revealed prominent extrasynaptic membrane AKAP150 labeling with less labeling at the PSD. The label was at greater distances from the spine membrane for AKAP150 CS than WT in the PSD but not in extrasynaptic locations. Immunogold EM of GFP-tagged AKAP79 WT showed that AKAP79 adopts a vertical, extended conformation at the PSD with its N-terminus at the membrane, in contrast to extrasynaptic locations where it adopts a compact or open configurations of its N- and C-termini with parallel orientation to the membrane. In contrast, GFP-tagged AKAP79 CS was displaced from the PSD coincident with disruption of its vertical orientation, while proximity and orientation with respect to the extra-synaptic membrane was less impacted. Single-molecule localization microscopy (SMLM) revealed a heterogeneous distribution of AKAP150 with distinct high-density, nano-scale regions (HDRs) overlapping the PSD but more prominently located in the extrasynaptic membrane for WT and the CS mutant. Thick section scanning transmission electron microscopy (STEM) tomography revealed AKAP150 immunogold clusters similar in size to HDRs seen by SMLM and more AKAP150 labeled endosomes in spines for WT than for CS, consistent with the requirement for AKAP palmitoylation in endosomal trafficking. Hidden Markov modeling of single molecule tracking data revealed a bound/immobile fraction and two mobile fractions for AKAP79 in spines, with the CS mutant having shorter dwell times and faster transition rates between states than WT, suggesting that palmitoylation stabilizes individual AKAP molecules in various spine subpopulations. These data demonstrate that palmitoylation fine tunes the nanoscale localization, mobility, and trafficking of AKAP79/150 in dendritic spines, which might have profound effects on its regulation of synaptic plasticity.